The Economic Crisis : Did Financial Supervision Matter? - Quintyn, Marc (IMF Working Papers; Working Paper, 2011)
The Asian financial crisis marked the beginning of worldwide efforts to improve the effectiveness of financial supervision. However, the crisis that started in 2007?08 was a crude awakening: several of these improvements seemed unable to avoid or mitigate the crisis. This paper brings the first systematic analysis of the role of two of these efforts - modifications in the architecture of financial supervision and in supervisory governance - and concludes that they were negatively correlated with economic resilience. Using the emerging distinction between macro- and micro-prudential supervision, we explore to what extent two separate institutions would allow for more checks and balances to improve supervisory governance and, thus, reduce the probability of supervisory failure.